Penguatan Sistem Manajemen Risiko Keamanan Pangan bagi RPA CV. Satria Jaya Pandaan Pasuruan - Windyarti, Puput; Rosyidi, Khafizh; Nuriyanto (Yayasan Pusat Kemanusiaan dan Transformasi Sosial, 2024)
The chicken meat processing agro-industry at the Slaughterhouse (RPA) plays a key role in ensuring safe animal protein for consumption. Processed chicken products are classified as high risk, thus food safety risk mitigation becomes critical. This community service program aims to assist the partner in identifying, measuring, and analyzing critical risk factors in chicken meat production using the Failure Mode Effect and Criticality Analysis (FMECA) approach. Conducted at RPA CV. Satria Jaya in Pasuruan, the program applied both quantitative-descriptive and participatory approaches. Results reveal that immersion before chickens are fully dead, lack of certification among halal slaughterers (JULEHA), and negligence in reciting basmalah during slaughtering are the most critical risks. Suggested improvements include adjusting pre-soaking duration, recruiting competent JULEHA, and developing a process control information system. These findings are expected to support the reinforcement of food safety risk management systems in the partner's slaughterhouse.